The Effect of Joko Widodo’s Political Marketing Communication in Instagram on His Image and Reputation in the Eyes of Millennial Generation in Jakarta - Nur Kholisoh; Siti Muslichatul Mahmudah (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2020)
This research aims to  study the effect of Joko Widodo's political marketing communication in Instagram on his image and reputation in the eyes of  millennial generation in the 2019 Indonesian Presidential Election. The theory used in this research is the Stimulus Organism Response, Persuasion Message Theory in political communication and theories or concepts of  reputation and image. The paradigm used is positivist with a quantitative approach. This research uses a survey method with a questionnaire as a data collection instrument to obtain information from a number of millennials as respondents aged between 19 and 39 years and participating in the 2019 Presidential Election with a total number of around 2,885,000.  Determination of sample size uses the Slovin formula with a margin of error of  5%, so the number of samples is 400 people. The sampling technique uses proportional sampling, while the data analysis technique uses path analysis. The results showed that political marketing communication has a direct effect on reputation at 11.9%. The image has a direct effect on reputation at 83.5%, and the indirect effect of marketing communication through image on reputation is 69.97%.